Book Review Evolution of Dam Policies: Evidence from the Big Hydropower States - Duncan, Jessica (International Journal of Water Governance, 2015)
By Scheumann, W., and O. Hensengerth. 2014. Heidelberg: Springer. ISBN: 978-3-642-23402-6